Risk of Fecal Incontinence Following Receptive Anal Intercourse: Survey of 21, 762 Men Who Have Sex with Men. Issue 11 (10th October 2021) - Garros, Aurélien; Bourrely, Michel; Sagaon-Teyssier, Luis; Sow, Abdourahmane; Lydie, Nathalie; Duchesne, Lucie; Higuero, Thierry; Damon, Henri; Velter, Annie; Abramowitz, Laurent
ABSTRACT: Background: The prevalence of receptive anal intercourse (RAI) is increasing. A few studies, with heterogeneous designs, have investigated the associated risk of fecal incontinence (FI). Aim: The primary objective of this study was to determine FI prevalence in a population of men who have sex with men (MSM) engaging in RAI. The secondary objective was to identify risk factors for severe FI. Methods Outcomes: An online survey of 24, 308 MSM was performed in 2019. Demographic and socioeconomic data were collected, together with information about RAI sexual practices, and FI defined by: "During the last month, have you experienced any involuntary leakage of stools?" Results Clinical Implications: In total, 1, 734 (8%) of the 21, 762 participants reported FI. Mean age was 35.3 years. The prevalence of FI was correlated with RAI frequency: 12.7% (if RAI ≥ 1 /wk) versus 5.7% (if no RAI). In multivariate analysis, the factors associated with FI were age (OR: 1.01), low socioeconomic status (OR 1.32 to 1.40), HIV-seropositivity (OR: 1.78), high RAI frequency (OR: 1.64), chemsex (OR: 1.67) and fist-fucking (OR: 1.61). Strengths and Limitations: Main strengths of our study are population size and assessment of detailed modalities of sexual practices. Main limitations are the use of a convenience non-random sample and the assessment of FI only during the past month. CONCLUSION: This study of a large MSM population, highlights risk factors for FI among RAI practices: RAI ≥ 1 /wk, chemsex, fist-fucking, low socioeconomic status.